Apraxia of Lid Opening in Subthalamic Nucleus Deep Brain Stimulation for Parkinson's Disease—Frequency, Risk Factors and Response to Treatment. Issue 4 (12th April 2021) - Krishnan, Syam; Shetty, Kuldeep; Puthanveedu, Divya Kalikavil; Kesavapisharady, Krishnakumar; Thulaseedharan, Jissa Vinoda; Sarma, Gangadhara; Kishore, Asha
ABSTRACT: Background: New‐onset apraxia of lid opening (ALO) is reported to occur in Parkinson's disease (PD) patients following Deep Brain Stimulation (DBS). There are only few systematic studies on this uncommon disorder of eyelid movements. Objectives: We aimed to examine the frequency, temporal evolution, predisposing factors and response to treatment, of new‐onset ALO in PD patients who underwent bilateral subthalamic nucleus (STN) DBS. Methods: We retrospectively reviewed the data of patients who underwent STN DBS at our centre between 1999 and 2017, with a minimum of 2 years of follow up after surgery. Results: New‐onset ALO was seen in 17 (9.1%) of the 187 patients after an average of 16.9 months (Range ‐ 6–36 months). Comparison of the groups with and without ALO revealed that ALO occurred more often in older patients, both at the onset of PD symptoms and at surgery and in those with non‐tremor dominant subtypes of PD and freezing of gait at baseline. The extent of levodopa dose reduction after surgery and the pre‐operative severity of motor symptoms were not risk factors. Response to adjustments of dopaminergic medications and stimulation parameters was ill‐sustained or nil. Botulinum toxin therapy resulted in satisfactory improvement in the majority. Conclusions: New‐onset ALO is an uncommon phenomenon that manifests months after STN DBS. Development of ALO is likely to be due to the effects of chronic stimulation of basal ganglia‐thalamo‐cortical or brain stem circuits controlling lid movements in susceptible patients. Botulinum toxin therapy offers relatively better relief of symptoms than other strategies.